Pengaruh Pertumbuhan Perusahaan, Komite Audit, dan Kepemilikan Manajerial Terhadap Kualitas Laba - Ardhea Pramitha Cahyani; Fitri Romadhon; Alfiana Fitri (P3M Politeknik Negeri Bengkalis, 2025)
The objective of this study is to examine the influence of company growth, audit committee composition, and managerial ownership on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period spanning 2020 to 2022. The purposive sampling method was employed to identify a sample of 30 companies, resulting in 90 observations. The data were obtained from financial reports published on the official IDX website. The data analysis was performed using multiple linear regression with SPSS software. The results demonstrated that company growth has a significant negative effect on earnings quality. However, the audit committee and managerial ownership were found to have no significant effect on earnings quality. This study provides empirical evidence that company growth can reduce earnings quality, while the effectiveness of the audit committee and managerial ownership require further investigation.